2022
DOI: 10.4168/aair.2022.14.2.233
|View full text |Cite
|
Sign up to set email alerts
|

The TL1A-DR3 Axis in Asthma: Membrane-Bound and Secreted TL1A Co-Determined the Development of Airway Remodeling

Abstract: Purpose Tumor necrosis factor-like ligand 1A (TL1A), especially its secreted form, has been shown to contribute to eosinophilic inflammation and mucus production, cardinal features of asthma, through its receptor, death receptor 3 (DR3). However, the role of the TL1A-DR3 axis in asthma, especially in terms of airway remodeling, has not yet been fully understood. Methods The present study investigated the expression and secretion of TL1A in the lung and human bronchial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…It has been found to act importantly in inflammatory bowel disease, neuroimmunity, and neuroinflammation 10 . Besides, TL1A can mediate the activation of downstream signals like NLRP3 through TNFRs 11 . NLRP3 plays a positive regulatory role in the A1 differentiation of RAs, 12 while it remains unknown whether TL1A is associated with the RA differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found to act importantly in inflammatory bowel disease, neuroimmunity, and neuroinflammation 10 . Besides, TL1A can mediate the activation of downstream signals like NLRP3 through TNFRs 11 . NLRP3 plays a positive regulatory role in the A1 differentiation of RAs, 12 while it remains unknown whether TL1A is associated with the RA differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Airway resistance of mice was measured within 24 hours after the last challenge, and the assessment methods were performed as previously described by our research team. 19 All mice were euthanized 24 hours after the last exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, PC-specific clearance of XBP1 can produce similar symptoms of spontaneous ileitis, suggesting that the PC-specific UPR plays an important role in maintaining ileal mucosal homeostasis in mice[ 124 ]. Xbp1 knockout in the mouse epithelium resulted in spontaneous enteritis in mice[ 125 ]. Pathological analysis showed that the deletion of Xbp1 resulted in endoplasmic reticulum stress and a lack of lysozyme and α-defensin expression in PCs[ 125 ].…”
Section: Pc Abnormalities Mediated By Susceptibility Genes and Microe...mentioning
confidence: 99%
“…Xbp1 knockout in the mouse epithelium resulted in spontaneous enteritis in mice[ 125 ]. Pathological analysis showed that the deletion of Xbp1 resulted in endoplasmic reticulum stress and a lack of lysozyme and α-defensin expression in PCs[ 125 ]. Therefore, XBP1 may play a partially compensatory role in inhibiting proinflammatory signals, maintaining mucosal homeostasis and assisting PC function in mice, thus supporting the function of PCs[ 126 ].…”
Section: Pc Abnormalities Mediated By Susceptibility Genes and Microe...mentioning
confidence: 99%